Community perception of traditional circumcision in a sub-region of the Transkei, Eastern Cape, South Africa - Meel, BL (South African family practice, 2005)
The ritual of traditional male circumcisions (initiation) of young adults goes back generations among Xhosa people of South Africa. Xhosa tribe is committed to preserving the old cultural traditions. Recently, this ritual has been tarnished by serious complications that have occurred, leading to amputation of penis and even death of initiates. To estimate the community perception of traditional circumcision, an interview of 100 subjects was carried out. About 67% were unaware of risks of traditional surgery and 16% unsure about any existed risk. Only 17% knew about risks associated with it. Sixty-three percent favoured traditional surgeons and 13% medical practitioners. No opinion was given by 24%. Traditional surgeons and the community must be aware of the risks associated with traditional circumcision.